prove this...........
Attachments:
![](https://hi-static.z-dn.net/files/d8b/94189b27b976db2f46cff7a3a11e38b3.jpg)
Answers
Answered by
1
Here is ur answer
Hope u understand
Thanx ☺️
Attachments:
![](https://hi-static.z-dn.net/files/d53/eb35295a6bde7317400bd8356393586c.jpg)
Answered by
0
Answer:if you can
mark me i need
Step-by-step explanation:
The answer is here,
Given that,
= > \: \frac{a + ib}{c + id} = p + iq
We can replace the " i " as " -i ".
= > \frac{a - ib}{c - id} = p - iq
Similar questions